Participatory research approaches in long-term care facilities for older adults: a meta-ethnography - Sophie Nadia Gaber; Manuel Guerrero; Lena Rosenberg (International Journal of Qualitative Studies on Health & Well-Being)
Purpose There is growing interest in the potential of participatory research approaches to democratize research, empower participants and contribute to targeted health and social care. Participatory research approaches are emphasized in ethical and funding applications regarding patient and public involvement; however, less is known about their use in long-term care facilities for older adults. This meta-ethnography seeks to provide an increased understanding and novel conceptualization of participatory research approaches in long-term care facilities for older adults. Methods A meta-ethnography was used to synthesize qualitative literature on participatory research approaches in long-term care facilities for older adults. In total, 1,736 articles were screened at title and abstract level, 35 studies were eligible for full-text review and 10 articles were included. Results The following third-order constructs were identified as salient to the conceptualization and use of participatory research approaches in long-term care facilities for older adults: 1) participatory backdrops, 2) collaborative places, 3) seeking common ground and solidarity, 4) temporal considerations, and 5) empowerment, growth, and cultural and social change. Conclusion This meta-ethnography contributes a novel conceptualization and six recommendations to enhance the design and implementation of participatory research approaches as democratic spaces of exchange and collaboration for older adults.